Integrated enzymes activity and transcriptome reveal the effect of exogenous melatonin on the strain degeneration of Cordyceps militaris - Zu, Zhichao; Wang, Siqi; Zhao, Yingming; Fan, Wenli; Li, Tianlai (Frontiers in Microbiology, 2023)
Cordyceps militaris, as a valuable medicinal and edible fungus, has been industrialized and has broad development prospects because C. militaris contains a lot of bioactive compounds benefit to our health. However, during the process of artificial cultivation, strain degradation is a bottleneck problem that hinders the industrialization of C. militaris. Previous studies showed that exogenous melatonin (MT) could scavenge reactive oxygen species in fungus and might alleviate the strain degradation. In order to explore the role and molecular mechanism of MT on strain degradation, the third generation strain “W5-3” of C. militaris was investigated by morphological, biochemical and transcriptomic approaches under MT treatment. Morphological observation showed that the colony angulation of C. militaris was significantly weakened, and the aerial hypha was reduced by 60 µmol·L-1 MT treatment,. Biochemical index indicated the accumulation of reactive oxygen species and malondialdehyde became slow. RNA-Seq revealed that a large number of antioxidant enzymes related genes were up-regulated under 60 µmol·L-1 MT treatment compared with the control. Among them, Glutathione S-transferase genes were up-regulated by 11.04 times; In addition, genes related to the synthesis of cordycepin and adenosine, and cell synthesis were also up-regulated, which were potentially involved in the biosynthesis of active compounds, and the growth and development of mycelium. Taken together, all these results provided the basis for further elucidating the molecular mechanism of strain degradation for .C. militaris.